2011
DOI: 10.1007/s12640-011-9250-2
|View full text |Cite
|
Sign up to set email alerts
|

The Activation of NMDA Receptor–ERK Pathway in the Central Amygdala is Required for the Expression of Morphine-Conditioned Place Preference in the Rat

Abstract: Reinforcing effects of addictive drugs can be evaluated with the conditioned place preference (CPP) test which involves both the action of drugs and environmental cues. However, the encoded neural circuits and underlying signaling mechanism are not fully understood. In this study, we have used morphine-CPP model in the rat and characterized the role of N-methyl-D: -aspartate (NMDA) receptor and the phosphorylation of extracellular signal-regulated kinase (ERK) in the central nuclei of amygdala (CeA) in the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 30 publications
1
21
0
1
Order By: Relevance
“…Recent evidence increasingly suggests that the amygdala including CeA is part of the brain's reward circuitry and is important also in regulation of positive emotions represented by reward-related responses (Baxter and Murray, 2002; See et al, 2003). The role of amygdala including CeA in behaviors of opioid reward has been shown in a number of studies and the receptor and signaling systems involved include NMDA receptors, cannabinoid CB1 receptors, dopamine receptors, neurokinin-1 receptors, ERK and PKMzeta (Gadd et al, 2003; Zarrindast et al, 2003; Rezayof et al, 2007; Li et al, 2008; Bishop et al, 2011; He et al, 2011; Li et al, 2011; Rezayof et al, 2011). However, local injection of morphine into the lateral nucleus of the amygdala did not induce CPP (Olmstead and Franklin, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence increasingly suggests that the amygdala including CeA is part of the brain's reward circuitry and is important also in regulation of positive emotions represented by reward-related responses (Baxter and Murray, 2002; See et al, 2003). The role of amygdala including CeA in behaviors of opioid reward has been shown in a number of studies and the receptor and signaling systems involved include NMDA receptors, cannabinoid CB1 receptors, dopamine receptors, neurokinin-1 receptors, ERK and PKMzeta (Gadd et al, 2003; Zarrindast et al, 2003; Rezayof et al, 2007; Li et al, 2008; Bishop et al, 2011; He et al, 2011; Li et al, 2011; Rezayof et al, 2011). However, local injection of morphine into the lateral nucleus of the amygdala did not induce CPP (Olmstead and Franklin, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated the important role of amygdala, including CeA and basolateral amygdala (BLA), in opioid reward. Activation of CeA NMDA receptors increases low-dose morphine-induced CPP (Rezayof et al, 2007) and the signaling pathway of NMDA receptor–extracellular signal-regulated kinase (ERK) in CeA is critical for expression of morphine CPP and for enhanced morphine CPP (incubation of morphine craving) after morphine withdrawal (Li et al, 2008; Li et al, 2011). Recently, He et al found that blockade of protein kinase M zeta (PKMzeta) in BLA, but not in CeA, inhibits morphine CPP (He et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is possible that exposure to and/or performance in the discrimination task alone activated ERK 1/2 expression in the central amygdala, and that alcohol-administration further potentiated that level. This is plausible given that the MAPK pathway is critically involved in learning and memory-associated plasticity processes [13, 17], and that the ERK pathway specifically in the amygdala has been shown to regulate memory consolidation [46] and the expression of drug-related cue learning [8, 9, 47]. Indeed, rats trained with the -opioid receptor agonist (U-50,488H) as a discriminative stimulus have greater pERK 1/2 levels in the central amygdala relative to drug-matched controls (i.e., nondiscrimination-trained) [48], suggestive of a learning-induced adaptation in pERK 1/2 .…”
Section: Discussionmentioning
confidence: 99%
“…NR2B-containing NMDA-R antagonists are capable of reducing the expression of morphine CPP when they are administered during opiate abstinence (without explicit extinction training) (Ma et al 2011b). They are also capable of preventing reinstatement of morphine CPP (Fujio et al 2005) g. NMDA-R in mPFC on reward h. NMDA-R in CeA on reward Li et al 2008;Li et al 2011a), on aversion (Watanabe et al 2002;Glass et al 2008) i. AMPA-R in CeA on aversion (Watanabe et al 2002) j. NMDA-R in Hipp on reward Ma et al 2007 for NR2B-containing NMDA-Rs), on aversion (Hou et al 2009) k. AMPA-R in Hipp on aversion (Hou et al 2009), on extinction (Billa et al 2009 for phospho-GluR1) l. NMDA-R in VTA on reward (Popik and Kolasiewicz 1999;Harris et al 2004), on reinforcement (Xi and Stein 2002) m. AMPA-R in VTA on reward (Harris et al 2004;Shabat-Simon et al 2008;Carlezon et al 1997 for GluR1-containing NMDA-Rs), on reinforcement (Xi and Stein 2002) n. mGluR2/3 in VTA on seeking (Bossert et al 2004) Note: Although mGluR5s have been shown to produce effects on opiate reward and reinforcement when administered systemically, their loci of action in the brain have not been identified, and are therefore not depicted here. Glutamate systems controlling opiate addiction.…”
Section: Extinction and Reinstatementmentioning
confidence: 99%
“…1h,i) (Watanabe et al 2002;Rezayof et al 2007;Glass et al 2008). NMDA-Rs within the CeA are also capable of controlling the expression of CPP, and the downstream activation of ERK is required for this effect Li et al 2008Li et al , 2011a. The CeA is an output station to midbrain targets implicated in the aversive state that accompanies opiate withdrawal, including the VTA (Zahm et al 2011) and periaqueductal gray (PAG) (Rizvi et al 1991) (Fig.…”
Section: Amygdala Outputsmentioning
confidence: 99%